Aldehyde Dehydrogenase 2 Has Cardioprotective Effects on Myocardial Ischaemia/Reperfusion Injury via Suppressing Mitophagy - Ji, Wenqing; Wei, Shujian; Hao, Panpan; Xing, Junhui; Yuan, Qiuhuan; Wang, Jiali; Xu, Feng; Chen, Yuguo (Frontiers in Pharmacology, 2016)
Mitophagy, a selective form of autophagy, is excessively activated in myocardial ischemia/reperfusion (I/R). The study investigated whether aldehyde dehydrogenase (ALDH2) exerted its cardioprotective effect by regulating mitophagy. Myocardial infarct size and apoptosis after I/R in rats were ameliorated by Alda-1, an ALDH2 activator, and aggravated by ALDH2 inhibition. Both in I/R rats and hypoxia/reoxygenation H9C2 cells, ALDH2 activation suppressed phosphatase and tensin homolog-induced putative kinase 1 (PINK1)/Parkin expression, regulating mitophagy, by preventing 4-hydroxynonenal and reactive oxygen species accumulation. Furthermore, the effect was enhanced by ALDH2 inhibition. Thus, ALDH2 may protect hearts against I/R injury by suppressing PINK1/Parkin–dependent mitophagy.